Pengembangan Pop Up Book Kontekstual pada Materi Teorema Pythagoras - Clara Anggun Fadhilla; Dwi Laila Sulistiowati (Universitas Ma'arif Lampung, 2026)
The development of engaging and relevant learning media is a solution to the low level of student engagement in understanding abstract mathematical concepts. This study describes the design process for a Pythagorean Theorem pop-up book media, synergized with a contextual approach. The research procedure uses a Research and Development (R&D) approach, based on the seven stages of the Borg and Gall model, including needs analysis through final product refinement. Through validation instruments and response questionnaires, this study found that the product was considered highly valid by material experts and media experts. The positive response from students also strengthened the media's position as a practical learning tool. These findings confirm that contextual pop-up books are highly suitable for supporting a more effective understanding of mathematical concepts.